Sorption of fluorescent polystyrene microplastic particles to edible seaweed Fucus vesiculosus - Sundbæk, Kasper Bjerrum; Koch, Ida Due Würtzner; Villaro, Clara Greve; Rasmussen, Niclas Spangegaard; Holdt, Susan Løvstad; Hartmann, Nanna B. (Journal of applied phycology, 2018)
Increased global demands for food have raised interest for seaweed as a healthy and sustainable food source. At the same time, the large amounts of microplastic in the oceans have raised concern in relation to pollution of seafood including sea vegetables. The aim of this study was to examine sorption of fluorescent polystyrene (PS) microplastic particles to edible macroalga (seaweed) Fucus vesiculosus , and to investigate to what extent adsorbed PS particles could be washed off, using an industrial relevant method. PS microplastic particles (diameter of 20 μm) were used in a concentration of 2.65 mg L −1 (corresponding to 597 particles per mL) in filtrated seawater (50 mL) to treat F . vesiculosus distal tips in blue cap flasks (100 mL) placed in a rotary box for 2 h. Results showed sorption of PS microplastic particles to F . vesiculosus analysed by microscopy and a significant reduction of 94.5% by washing. These results were based on high microplastic concentrations, not comparable to natural conditions/concentrations. Nonetheless, this study provides methodological and mechanistic insights into procedures for investigating the sorption of microplastics to seaweed, for which there is currently no established standardised method.